Network Lifetime Maximization in Delay-Tolerant Sensor Networks with a Mobile Sink - Zichuan Xu; Weifa Liang; Yinlong Xu (2012 IEEE 8th International Conference on Distributed Computing in Sensor Systems, 2012)
In this paper we investigate the network lifetime maximization problem in a delay-tolerant wireless sensor network with a mobile sink by exploiting a nontrivial tradeoff between the network lifetime and the data delivery delay. We formulate the problem as a joint optimization problem that consists of finding a trajectory for the mobile sink and designing an energy-efficient routing protocol to route sensing data to the sink, subject to the bounded delay on data delivery and the given potential sink location space. Due to NP-hardness of the problem, we then propose a novel optimization framework, which not only prolongs the network lifetime but also improves the other performance metrics including the network scalability, robustness, and the average delivery delay. We finally conduct extensive experiments by simulations to evaluate the performance of the proposed algorithm against other heuristics. The experimental results demonstrate that the proposed algorithm outperforms the others significantly in terms of network lifetime prolongation.